Multi-target Tracking in a Test Range Scenario - Bhattacharya, Shrabani; Raj, R. Appavu (Defence Science Journal, 2007)
Integrated Test Range (ITR) handles various types of multiple-target flight trials. To facilitatetarget tracking and estimation in such multi-target scenario, nearest neighbourhood (NN)technique-based data association algorithm has been adopted at ITR. The present paper discussesthe NN-based data association algorithm and its performance in a real flight trial situation byusing multiple-target track data from a multi-target tracking radar.